Connection Innovation and Development Bank Sharia as well as Evolution Development and Innovation Contract and Islamic Banking Products - Devi Dwi Anggraini; Akhmadi, Slamet; Filzah Talitha; Tsania Zuhrotunisa (Faculty of Islamic Economics and Business, UIN Prof. K. H. Saifuddin Zuhri Purwokerto, 2022)
In the increasingly fierce competition in Islamic banking, product innovation is becoming more and more important key in increasing competitiveness and spurring company growth, because it is important for Islamic banks to know what factors can influence development and innovation product banking sharia and build Micro small and Medium Enterprises for resolve poverty in Indonesia .factor which influence innovation products can come from internal or external, internal factors mean the organization of all something in inside like Human Resources, culture company, and strategy company, while factor external in cause by growth market, level competition, regulation bank Indonesia, OJK, and fatwa National Sharia Council.